Exploring the first-year experiences of international students in a multicultural institution in the United Arab Emirates - Qiqieh, Sura; Regan, Julie-Anne (Journal of International Students, 2023)
This study aimed to explore the factors reported by first-year international students which helped or hindered their experiences of transition to a multicultural higher education institution in the United Arab Emirates. Descriptive phenomenology was used to portray participants constructed and co-constructed views, formed through their individual and social experiences of transitioning to international higher education. Six focus group interviews were used to collect data from international students to access a wide variety of nationalities. The qualitative data were analyzed using an inductive approach. Three themes emerged as being significant to their transitional experiences: students' experiences of freshmen orientation, their academic experiences, and the institutional environment. Researching international students' experiences of transitioning to higher education in the United Arab Emirates, and even generally in the Middle East, constitutes an original context. The context of this study also offers originality because the international students are in the majority rather than the minority.